Trends in the Development of the Transport Industry Through the Prism of Artificial Intelligence - Tuparova, Stela (Research Papers, 2025)
This study is dedicated to analyzing the short-term evolutionary and long-term revolutionary transformations within the economic sector, with a specific focus on the transport industry, through the prism of artificial intelligence. The escalating demands of an increasingly globalized world underscore the urgent need for comprehensive reforms across the industry. These reforms must be supported by innovative solutions capable of producing a broad-scale impact and delivering measurable results within a short time frame. The central thesis of this report emphasizes the transformative potential of artificial intelligence as a key enabler of change. Unlike conventional approaches that often yield gradual improvements, AI possesses the capacity to accelerate progress and generate tangible benefits in the short term.